Implementasi Supervisi Pendidikan Agama Islam di Madrasah Ibtidaiyah Negeri 5 Jember - Mohammad Syafi’I (JURNAL PENDIDIKAN DAN KAJIAN ASWAJA, 2022)
National Education functions to develop abilities and form a dignified national disposition and civilization in order to educate the nation's life, aiming to develop the potential of students to become human beings who have faith and devotion to God Almighty, have a noble character, are healthy, knowledgeable, capable, creative, independent and become democratic and responsible citizens. This study uses a descriptive-qualitative approach, which is a research procedure that produces descriptive data in the form of written or spoken words from respondents or people whose behavior is observed. This research describes various things related to the focus of the problems raised. Data collected through observation and interviews. Educational supervision is carried out using super-vision individual techniques, namely class observation and class visits. Meanwhile, group supervision techniques such as group discussions, supervision meetings, seminars, workshops and workshops are difficult to do Keywords: Implimentation, Supervision And Islamic Religious Education